IMPLEMENTASI HADITS NABAWI TERHADAP ETIKA MAKAN DAN MINUM (KAJIAN LIVING HADIS) - Nuha, Nazahah Ulin; Anggraeni, Ninda dwi (LPPM STAI Muhammadiyah Probolinggo, 2023)
In the verses of the Qur'an, Allah swt has explained that one of the greatest blessings besides health that Allah has given is food and drink. Regarding the ethics of eating and drinking, the Messenger of Allah (PBUH) has given an example which is mostly intended for the benefit of his ummah. According to the companions of the Prophet, it is an ideal reference that must be followed and practiced. The literature review method is the method used by the author in the preparation of research, where the author collects various types of information from the library, such as books, and documents, with the aim of finding different theories and ideas and after that the results are formulated. according to the research objectives. According to the companions of the Prophet, it is an ideal reference that must be followed and practiced. The habits of the Prophet are a description of the values contained in the Qur'an. The description of the Prophet's diet as an ideal reference can be seen from the hadith. As the Prophet did not encourage his people to eat and drink while standing and eat food from those closest to him and use his right hand. All of this shows that Islamic law, if implemented consistently and correctly, will go hand in hand with the concept of a healthy life that has been explained by health and medical science.